Accuracy of sonographic fetal gender determination: predictions made by sonographers during routine obstetric ultrasound scans. Issue 3 (August 2014) - Kearin, Manette; Pollard, Karen; Garbett, Ian
Abstract: Objectives : The purpose of this study was to determine the accuracy of sonographer predictions of fetal gender during routine ultrasounds. Primarily, the study sought to investigate the accuracy of predictions made in the first trimester, as requests from parents wanting to know the gender of their fetus at this early scan are becoming increasingly common. Second and third trimester fetuses were included in the study to confirm the accuracy of later predictions. In addition, the mother's decision to know the gender was recorded to determine the prevalence of women wanting prenatal predictions. Methods : A prospective, cross sectional study was conducted in a specialist private obstetric practice in the Illawarra, NSW. A total of 640 fetuses across three trimesters were examined collectively by seven sonographers. Fetal gender was predicted using the sagittal plane only in the first trimester and either the sagittal or transverse plane in later trimesters. Phenotypic gender confirmation was obtained from hospital records or direct telephone contact with women postnatally. Results : Results confirmed 100% accuracy in predictions made after 14 weeks gestation. The overall success rate in the first trimester group (11–14 weeks) was 75%. When excluding those scans where a prediction could not be made, success rates increased to 91%. Results were less accurate for fetuses younger than 12 weeks, with an overall success rate of 54%. Male fetuses under 13 weeks were more likely to have gender incorrectly or unable to be assigned. After 13 weeks, success rates for correctly predicting males exceeded that of female fetuses. Statistical differences were noted in the success rates of individual sonographers. Sixty seven percent of women were in favour of knowing fetal gender from ultrasound. Publicly insured women were more likely to request gender disclosure than privately insured women. Conclusions : Sonographic gender determination provides high success rates in the first trimester. Results vary depending on sonographer experience, fetal age and fetal gender. Practice guidelines regarding gender disclosure should be developed. Predictions prior to 12 weeks should be discouraged.